Barriers and facilitators of health among older adult immigrants in the United States: an integrative review of 20 years of literature - Maren M. Hawkins; Daniel D. Holliday; Lance S. Weinhardt; Paul Florsheim; Emmanuel Ngui; Tala AbuZahra (BMC, 2022)
Abstract Background There are over seven million older adult immigrants in the United States, and that number is expected to increase. Older adult immigrants in the United States have unique factors that influence their health. Methods In this integrative review, we systematically review 20 years of peer-reviewed literature on the barriers (i.e. isolation, lack of English Language Proficiency, low health literacy, lack of SES resources, discrimination) and facilitators (i.e. English Language Proficiency and maintaining ones native language, social support, culturally sensitive providers, healthcare access) of health among older adult immigrants in the United States. Results We found differing uses of the term 'older adult', emphasis on the lack of homogeneity among older adult immigrants, social support and isolation as significant barriers and facilitators of older adult immigrant health, and inconsistencies in uses and definitions of acculturation. We also examined relevant theories in the literature. Based on the literature review, focusing on Acculturation Theory, Social Cognitive Theory, and Successful Aging Theory, combining these three theories with findings from the literature to create the Older Adult Immigrant Adapted Model for Health Promotion. Conclusions Public health strives to promote health and prevent adverse health outcomes. Our integrative review not only systematically and thoroughly explicates 20 years of literature, but the Older Adult Immigrant Adapted Model for Health Promotion, provides guidance for future research and interventions.